Integration of solar latent heat storage towards optimal small-scale combined heat and power generation by Organic Rankine Cycle. (June 2020) - Lizana, Jesus; Bordin, Chiara; Rajabloo, Talieh
Highlights: Solar ORC integration at operating temperatures between 80 °C and 140 °C. Comparison between sensible and latent heat storage alternatives. Simulation in TRNSYS for solar energy balance and ASPEN for ORC performance. Discussion of design criteria and requirements for an optimal implementation. Potential benefits of latent heat storage to improve solar ORC performance. Abstract: Thermal energy and distributed electricity demand are continuously increased in areas poorly served by a centralized power grid. In many cases, the deployment of the electricity grid is not economically feasible. Small-scale Organic Rankine Cycle (ORC) appears as a promising technology that can be operated by solar energy, providing combined heat and power (CHP) generation. Additionally, thermal energy storage can ensure stable and continuous operation in case of scarce thermal energy availability. This paper evaluates the potential application of latent heat storage to enhance solar ORC performance at operating temperatures between 80 °C and 140 °C, aiming at improving the efficiency and capacity of ORC for low-cost non-concentrating solar-thermal collectors. Three thermal energy storage scenarios are considered. Scenario 1 and 2 consist of reference cases based on a solar ORC system integrated with a conventional hot water tank and a pressurised water tank. Scenario 3 implements a storage unit based on a phase change material. The simulation was carried out through models developed in TRNSYS for solar energy balance and ASPEN for ORC system performance. The results show that solar latent heat storage tank can provide 54% of useful collector gains with a higher and narrower temperature range in the evaporator, increasing the annual thermal energy capacity by 19%, reducing annual heat losses by 66% and decreasing the investment cost by 50% in comparison with a pressurised water tank. It also allows increasing the efficiency of ORC cycle by approximately 18% (from 8.9% to 10.5%) with a higher net generated power than a conventional water tank integration, scaled up from 498 W to 1628 W. These results highlight the potential benefits that latent heat integration provides to improve the low-cost solar ORC performance for powering electricity and thermal energy supply.